OSTEOLOGICAL STUDY ON THE SPERM WHALE PHYSETER MACROCEPHALUS LINNAEUS FROM INDIAN OCEAN - James, P S B R; Soundararajan, R (Indian Journal of Fisheries, 2011)
The skeleton of a miafe sperm will? lie, Physeter macrocephalus Linnaeus(8.1 m) which was stranded on the southern side of Rmisadiai Island" (Gulf ofMannar) on 30th April 1980, is described in detail. The salient features are atrough-shaped asymmertrical skull, long 'V shaped mandible, a vertebral columnconsisting of seven cervical vertebrae (six of them fused, the first free), eleventhoracic vertebrae with only ten ribs, eight lumbar vertebrae and 23 caudal vertebraewith ten chevron bones attached between 3rd and 4th caudal vertebrae andfairly large forelimbs. Comparison of the skull of this specimen (8.1 m) with thatof another male of an estimated length of 17. 4 m did not reveal any essentialdifferences due to age. The osteofagical features in which the present material differsfrom others on record from elsewhere are mentioned.